Determinants of healthcare utilization under the Indonesian national health insurance system – a cross-sectional study - Qinglu Cheng; Rifqi Abdul Fattah; Dwidjo Susilo; Aryana Satrya; Manon Haemmerli; Soewarta Kosen; Danty Novitasari; Gemala Chairunnisa Puteri; Eviati Adawiyah; Andrew Hayen; Anne Mills; Viroj Tangcharoensathien; et al. (BMC Health Services Research)
Abstract Background Indonesia has implemented a series of healthcare reforms including its national health insurance scheme (Jaminan Kesehatan Nasional, JKN) to achieve universal health coverage. However, there is evidence of inequitable healthcare utilization in Indonesia, raising concerns that the poor might not be benefiting fully from government subsidies. This study aims to identify factors affecting healthcare utilization in Indonesia. Methods This study analysed cross-sectional survey data collected by the “Equity and Health Care Financing in Indonesia” (ENHANCE) Study. Andersen’s behavioural model of health services use was adopted as a framework for understanding healthcare utilization in Indonesia. Sociodemographic variables were categorized into predisposing, enabling and need factors. Outcome measures included the utilization of primary and secondary health services. Multi-level logistic regression models were run to examine factors associated with each type of health service utilization. Results Of the 31,864 individuals included in the ENHANCE survey, around 14% had used outpatient services in the past month. Fewer than 5% of the study population had visited hospitals for inpatient care and about 23% used maternal and child health services in the past 12 months. Age, gender and self-rated health were key determinants of health services utilization. No significant differences in primary care utilization were found among people with different insurance status, but people who received subsidised premiums under the JKN were more likely to receive primary care from public health facilities and less likely from private health facilities. Compared to people who pay JKN insurance premiums themselves, the uninsured and those whose premiums were subsidised by the government were less likely to visit public and private hospitals when other factors were controlled. Conclusion This study demonstrates that the distribution of healthcare utilization in Indonesia is largely equitable as predisposing factors (age and gender) and health need were found to greatly influence the utilization of different types of health services. However, enabling factors such as health insurance status were also found to be associated with inequity in utilization of hospital services. Further policy actions regarding resource allocation and health service planning are warranted to achieve a more equitable pattern of health service use in Indonesia.